Economic analysis of selected filter beds used for water treatment - Iwona Skoczko; Ewa Szatyłowicz; Łukasz Malinowski (Economic and Environmental Studies (E&ES), 2017)
The aim of the present study was to assess the possibility of use economic analysis to compare selected filter beds used in water treatment plant. There were considered selected masses which are commonly used for removal iron and manganese from the groundwater. Water purification with these minerals is one of the most important processes in water technology. Underground water taken by wells is polluted with increased concentration of iron and manganese. That is why many of individual, urban and also industrial water treatment plants do their best to remove them from the water. Thousands of tons of different filter masses set for iron and manganese purification from the water are bought on the Polish market every year. Tests carried out within experiments are presented in this paper, which include analysis of filter beds such as: Filtersorb FMH, Filter AG, Pyrolox and Defeman. Selected masses differ with origin, density, mesh size, diameter and price. For the complete economic analysis of the selected filters there considered the following factors affected the operating costs: cost of filter beds, environmental fees for water intake, costs of equipment to aerate the water, cost of chemical reagents for the regeneration of beds, cost of a dosing pump, costs of reagents for filter regeneration. The analysis showed that the cost of exploitation of the filter depends mainly on the purchase and filtration rate. In addition, significant parts in the costs of exploitation of the filter is environmental fee for water intake, but lower than buying filtration bed. The cheapest in the exploitation turned out to be Defeman and Filter-AG, the most expensive - Filter-FMH.
Keywords: Q51; Q52; 330; filter beds; economic analysis; water treatment; operating costs; filter bed